KONSUMSI MAKANAN DI DESA TERTINGGAL WILAYAH BOGOR, TANGERANG DAN BEKASI (BOTABEK) SEBAGAI DAMPAK KRISIS EKONOMI - Djoko Kartono; Anies Irawati; Amelia Amelia; Suhartato Suhartato (Persagi, 2000)
FOOD CONSUMPTION IN POOR VILLAGES OF BOGOR, TANGERANG AND BEKASI REGIONS AS THE IMPACT OF ECONOMIC CRISIS.Background: Socio-economic condition of population was deteriorated by economic crisis that hit Indonesia in mid of 1997 altogether with long wry season during 1997. Economic factors such as increase in the price of the daily needs, reduction in agricultural production and the level of income in rural areas, contraction in the construction sector in urban areas, depression in the manpower market altogether had negative impact to the welfare of the lower income population.Objective: The aim of the survey was to learn the nutrient intake of household in poor villages as the impact of economic crisis.Method: The Nutritional Consumption Survey in all villages of West Java Province was conducted at the end of 1996 and these data were used as baseline. Similar survey was conducted at the end of 1999 in Bogor City, Tangerang and Bekasi Districts as the follow-up data. Thirty villages in each district were selected randomly to include 10 poor villages and 20 non-poor category villages. In each village, one Posyandu that had been the location of 1996 survey was selected. Ten households that have under-five child were selected randomly in the Posyandu.Results: Household. Energy consumption in poor villages and non-poor category villages were higher before the crisis compared to during the crisis. Protein consumption in the non-poor villages before the crisis was similar to during crisis. Vitamin A consumption in non-poor and poor villages much lower during crisis compared to before crisis. Under-five children 1999. Energy, protein and fat intake of under-five children was similar between poor and non-poor category villages. Carbohydrate intake was significantly different between poor and non-poor category villages. Iron intake was similar before and during crisis.Conclusions: Economic crisis has negative impact on energy and protein consumption both poor and non-poor category villages before and during crisis. Energy and vitamin A intakes in poor and non-poor category villages reduced during crisis compared to before crisis.Recommendations: Nutritional improvement programs to overcome the impact of economic crisis should be directed to the poor villages. However, if the crisis remained continued the non-poor village should also be given attention.Key Words: nutrient, food consumption, household, poor villages, economic crisis.